Public policy: a new introduction - Knill, Christoph; Tosun, Jale (Textbooks in Policy Studies, 2020)
Intro -- List of Boxes -- Foreword to the Second Edition -- 1: Introduction -- WHAT IS A PUBLIC POLICY? -- Polity, Politics and Policy -- Elements of a Public Policy -- Differences in Scope: Sectors, Targets and Instruments -- ANALYTICAL PERSPECTIVES ON THE POLICY-MAKING PROCESS -- Basic Theoretical Perspectives on Public Policies: Rational Process Design, Muddling Through or Just Chance? -- Stages of the Policy Process -- OPPORTUNITIES AND CHALLENGES FOR POLICY-MAKING -- STUDYING PUBLIC POLICY: THE APPROACH AND STRUCTURE OF THIS BOOK -- Basic Analytical Tools, Concepts and Theories -- Stages of the Policy Process -- Cross-Cutting Themes -- 2: The Nature of Public Policies -- INTRODUCTION -- TYPOLOGIES OF PUBLIC POLICIES -- Classification by Implications for Politics -- Lowi's Policy Typology -- Wilson's Policy Typology -- Classification by Governance Principles and Instruments -- Nodality -- Authority -- Treasure -- Organization -- Alternative Schemes -- POLICY DIMENSIONS -- Policy Dimensions in the Sequence of the Policy Cycle -- Policy Content Dimensions -- POLICY STYLES -- CONCLUSIONS -- Further reading -- 3: The Context for Policy-Making: Central Institutions and Actors -- INTRODUCTION -- NATIONAL INSTITUTIONS: DEFINING THE RULES OF THE POLITICAL GAME -- Constitutions and Constitutional Courts -- Division of Powers -- Electoral Institutions and Party Systems -- INTERGOVERNMENTAL ORGANIZATIONS: GLOBAL PUBLIC POLICY -- The United Nations System -- The World Trade Organization -- KEY ACTORS -- Public Actors -- The Executive -- The Legislature -- The Judiciary -- The Bureaucracy -- Political Parties -- Private Actors -- Interest Groups -- Experts -- CONCLUSIONS -- Further reading -- 4: Theoretical Approaches to Policy-Making -- INTRODUCTION -- STRUCTURE-BASED MODELS -- The Cleavage Approach -- Varieties of Capitalism -- INSTITUTION-BASED MODELS.